-(1+n)=-1-n

Simple and best practice solution for -(1+n)=-1-n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(1+n)=-1-n equation:



-(1+n)=-1-n
We move all terms to the left:
-(1+n)-(-1-n)=0
We add all the numbers together, and all the variables
-(n+1)-(-1n-1)=0
We get rid of parentheses
-n+1n-1+1=0
We add all the numbers together, and all the variables
=0
n=0/1
n=0

See similar equations:

| 9r+6=46-r | | 5(10x+2)/10=7+5/10x | | 61x²=0 | | 3k+5=6k-4 | | 2j−2=2 | | 4x+14=74−6x | | 169=25+b^2 | | 3x+13=x+33 | | -7(-3n-8)=8(n+7)-n | | 9x+5=23-5x | | 11x-15.6=10.9 | | x+3.9=0.1(100+x) | | -(-2x+8)=5x+18 | | -3(z+2)=9z1+1 | | 14a+1=14.5 | | (√x^2+15−8)(√x^2+15+8)=0. | | x+0.1=0.045(100+x) | | (√x2+15−8)(√x2+15+8)=0. | | x^2+11x+24=0. | | 5k^2+29k=6 | | 40-22.5x=180 | | -4x+4x=6(-2+3x)-3(6x-1) | | 5(5x=7-3x) | | 15=24x+3 | | 3x-32=2x+18 | | -16-4x=4 | | 4v+715=6v+210 | | 51=x+31 | | 5(x-3)+7=4(x-1)-3 | | 5-3(x+2)=-4x+1 | | -2(x-17)=-20x-38 | | -2(2x-1)+3=-4x |

Equations solver categories